(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: Since its invention in the first quarter of the last century, diphtheria toxoid was successfully used for vaccination against diphtheria. However, sporadic case and even an epidemic have been recorded in many parts of the world, suggesting the presence of genetic factors influencing the immune response to this vaccine. Aim: To assess the role of three single nucleotide polymorphisms(miRNA-146a G> C, miRNA-49 T> G and miRNA-196a2 C> T) in miRNA genes in immune response to diph- theria vaccine. Subjects and Methods: This study recruited 68 children and adolescents who received three doses of diphtheria toxoid. DNA was isolated from the blood lymphocytes and miRNA- 146a,miRNA-149 and miRNA-196a2 genes were amplified, and then directly sequenced. Serum levels of anti-diphtheria toxoids IgG antibodies were determined by enzyme linked immunosorbent assay, and accordingly the immune response was categorized into good, moderate and low immunity .The association of different genotypes and alleles with immune status was illustrated statistically. Results: Good immune response to diphtheria vaccine was significantly associated with the C allele of the polymorphism miRNA-146a G> C. Out of 14 carriers of GG geno- type,11(78.57%)showed good immunity compared to only 48.15% of GG carriers who had such immunity (P=0.039).The mutant allele of miR-149 T> G was more prevalent than wild type allele G among subjects with good immunity .However, the difference was insignificant .Genotypes and allele frequencies of the SNP miR-196a2 C> T were very close in different immunological statuses. Conclusion: The results of the current study suggest the significant role of miRNA-146a G> C gene polymorphism and the insignificant role of both miRNA-149 T>G and miRNA- 196a2 C>T gene polymorphisms in response to diphtheria toxoids vaccine. More studies are required to find out the associations of different polymorphisms in miRNA genes with immune response for different vaccines.